Prevalence of back pain and its associated factors among government dental personnel in kelantan - Ab Samat, Razan (2011)
INTRODUCTION Dentistry is a high risk profession for the development of back pain as it requires high visual demands which result in the adoption of affixed and uncomfortable postures. This study was conducted to determine the prevalence and associated factors of back pain among government dental personnel in Kelantan. METHODS A cross sectional study was conducted among 350 dental personnel including dentist, dental nurse, technician and dental surgery assistant in all government dental clinics in Kelantan. Non probability sampling method was applied as all subjects were included in this study. A validated Branson Posture Assessment Instrument (BPAI) and direct observation of the subjects while performing their routine task were used. Proforma on sociodemographic and occupational characteristic was used. Descriptive statistics including mean and standard deviation for numerical and percentage for categorical data were calculated. Multiple logistic regression analysis was performed to determine factors associated with back pain. xv RESULTS From 350 respondents, majority were female (79.1%) and Malay (98.0%). Age of respondents ranged from 22 to 56 year old. The prevalence of back pain was 44.9% (95% CI: 39.65, 50.07). Dental technician gave the highest prevalence of back pain 52.4% (95% CI: 40.05, 64.71). Logistic regression analysis showed that after controlling for potential confounders, the significant risk factors associated with back pain were self reported abnormal posture (OR: 7.33, 95% CI: 3.19, 16.82) and job category (OR: 0.38, 95% CI: 0.20, 0.75). CONCLUSION The prevalence of back pain among Kelantan dental personnel was considered high. The significant risk factors associated with back pain were abnormal posture and job category. Innovations of ergonomically friendly dental equipment is one of the method to improve the work practice and health of the dental personnel.